2015
DOI: 10.1186/s40623-015-0224-0
|View full text |Cite
|
Sign up to set email alerts
|

ToF-SIMS analysis of carbonaceous particles in the sample catcher of the Hayabusa spacecraft

Abstract: Three carbonaceous category 3 particles (RA-QD02-0180, RB-QD04-0037-01, and RB-QD04-0047-02) returned in the sample catcher from the Hayabusa spacecraft were analyzed by time of flight-secondary ion mass spectrometry (ToF-SIMS) to establish an analytical procedure for determination of their origins. By the different analytical schemes, the three particles gave distinct elemental and molecular ions, in which the organic carbons commonly appear to be associated with nitrogen, silicon, and/or fluorine. The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
0
27
0
Order By: Relevance
“…RB-QD04-0047-02 also showed fine structures in the 1,729 to 965 cm −1 region. The absorption at 1,729 cm −1 is assigned to C = O stretching, and the absorption at 1,506 cm −1 is assigned to aromatic C = C. The absorption band at around 1,000 cm −1 may be by the Si-O stretching, corresponding to the Si in the sample Naraoka et al 2015). This will be discussed further along with the results from the white object in the 'The category 3 particles as thermally unaltered materials' section.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…RB-QD04-0047-02 also showed fine structures in the 1,729 to 965 cm −1 region. The absorption at 1,729 cm −1 is assigned to C = O stretching, and the absorption at 1,506 cm −1 is assigned to aromatic C = C. The absorption band at around 1,000 cm −1 may be by the Si-O stretching, corresponding to the Si in the sample Naraoka et al 2015). This will be discussed further along with the results from the white object in the 'The category 3 particles as thermally unaltered materials' section.…”
Section: Resultsmentioning
confidence: 99%
“…The observed Raman bands are suggested to be the reaction products during sample return and/or artifacts that may be induced by electron beam exposure. In addition, the presence of Si in RB-QD04-0047-02 Naraoka et al 2015) should be explained. It may be an addition like talc associated with Viton rubber.…”
Section: Comparison Between Category 3 Particles and Artificial Substmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the Raman spectra show disordered parameters associated with a low-maturity level, and hence, the particles are not associated with the Itokawa asteroid particles. Naraoka et al (2015) report TOF-SIMS analysis of three category 3 particles [only one in common with Ito et al (2014) and Kitajima et al (2015)] in order to determine elemental compositions. These analyses have proven to be difficult because the particles have been part of an extended analytical program, and in particular, the Cs primary ion beam used in the nano-SIMS analysis has pervaded the grain.…”
mentioning
confidence: 99%